Study on Determining PRH Locations for Flood and Drought Mitigation in Semarang Regency - Bambang Tutuko; Fitria Maya Lestari; Edy Susilo; Istianah Istianah (Universitas Nahdlatul Ulama Blitar, 2026)
Population growth, land-use conversion, and the reduction of vegetation cover have led to increasingly frequent floods and droughts in Semarang Regency. These conditions exacerbate surface runoff and reduce the soil’s capacity to store water, resulting in inundation during the rainy season and drought during the dry season. The objective of this study is to determine the location for installing Horizontal Recharge Pipes (HRP), which play an important role, particularly in flood-prone areas, by enhancing groundwater infiltration as a water reserve. The method applied in this research involves calculating the magnitude of runoff discharge in areas with potential flood inundation, which is then simulated with the application of HRP installation to determine the number of HRPs required to reduce flooding. Drought-prone areas were analyzed using satellite imagery to identify suitable HRP locations. In the Klegung watershed, 10 HRP units are required; in the Curug watershed, 460 units; and in the Lodong watershed, 835 units, all using a 12-inch diameter. Drought analysis using Landsat imagery identified dry areas in East Ungaran, Susukan, Suruh, Bancak, and Pringapus subdistricts. The installation points for HRPs can be prioritized based on areas experiencing inundation or drought. The implementation of HRPs is expected to infiltrate surface runoff effectively, thereby reducing flood risk while simultaneously increasing groundwater availability in Semarang Regency.